A compact optical fiber based gas sensing system for carbon dioxide monitoring - Razali, Muda; Norhana, Arsad; N., Ariffin; Amran, Abdul Hadi (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents an approach to develop and optical fiber based gas leak sensor that can be used to detect and quantify carbon dioxide gas. The developed sensor system operates based on the principles of IR absorption spectroscopy using dual channel and double wavelength method. Therefore, it is possible to eliminate the interference signal from the outside environment by using this method. The design of the CO2 gas sensor system consists of Broadband light source, two IR detectors with different NBP filters for Active and Reference channel, chalcogenide CIR fibers and a compact gas detection cell. The output of the sensor system is captured using in-house LabVIEW program with DAQ capabilities and displayed in real time. Experimental results show that the developed optical fiber based gas sensor system is capable to detect and quantify concentrations of carbon dioxide gas for leak detection and also environmental monitoring applications.